The contribution of the glenoid labrum to glenohumeral stability under physiological joint loading using finite element analysis. Issue 15 (18th November 2017) - Klemt, Christian; Nolte, Daniel; Grigoriadis, Grigorios; Di Federico, Erica; Reilly, Peter; Bull, Anthony M. J.
Abstract: The labrum contributes to passive glenohumeral joint stability. Cadaveric studies have demonstrated that this has position and load dependency, which has not been quantified under physiological loads. This study aims to validate subject-specific finite element (FE) models against in vitro measurements of joint stability and to utilise the FE models to predict joint stability under physiological loads. The predicted stability values were within ± one standard deviation of experimental data and the FE models showed a reduction in stability of 10–15% with high, physiological, loads. The developed regression equations provide the first representation of passive glenohumeral stability and will aid surgical decision-making.